Concentration of heavy metals in drinking water and health risk from semi-urban area / Noorfazira Mohamed @ Busu - Mohamed @ Busu, Noorfazira (Faculty Of Applied Sciences, 2017)
Heavy metals exposure was dangerous to human health and ecosystem. Reducing an exposure to the heavy metal especially through drinking water related with management of drinking water in communities is important. The objectives of this study were to determine the concentration of selected heavy metal (Cr, Cd, Zn and Pb) in drinking water and to estimate the health risk using health risk assessment (HRA). This study also carried out to identify the level of knowledge, attitude and practice (KAP) regarding heavy metal contamination in drinking water. The concentration of selected heavy metals was analysed by using Inductively Coupled Plasma Optical Emission Spectrometry (ICP-OES) and the information of KAP level was measured using a set of questionnaires. There was a potential noncarcinogenic health risks could be occurred from the Cd, Cr and Pb exposure via dermal contact (HQ>1). The carcinogenic health risk showed there was the greater probability of cancer to develop within population in study area of Cr compared to Pb. The population has good knowledge (58.44%) in term of water supply, quite low positive attitude (43.33%) on believing the dangerous of heavy metals contamination in drinking water and better practice (67.50%) in terms of drinking water management. Identifying the quality of drinking water through HRA and KAP could give more knowledge for the communities to improve the management of drinking water quality in the future. Therefore, it is strongly recommended the responsible authorities to take some corrective measures in order to decrease the level of heavy metals contamination in drinking water.